Coupled 3‐D stream flow and hyporheic flow model under varying stream and ambient groundwater flow conditions in a pool‐riffle system. Issue 9 (17th September 2013) - Trauth, Nico; Schmidt, Christian; Maier, Uli; Vieweg, Michael; Fleckenstein, Jan H.
<x xml:space="preserve">Abstract</x> [1] Exchange of water and solutes across the stream‐sediment interface is an important control for biogeochemical transformations in the hyporheic zone (HZ). In this paper, we investigate the interplay between turbulent stream flow and HZ flow in pool‐riffle streams under various ambient groundwater flow conditions. Streambed pressures, derived from a computational fluid dynamics (CFD) model, are assigned at the top of the groundwater model, and fluxes at the bottom of the groundwater model domain represent losing and gaining conditions. Simulations for different Reynolds numbers (Re) and pool‐riffle morphologies are performed. Results show increasing hyporheic exchange flows (m3/d) for larger Re and a concurrent decrease in residence time (RT). Losing and gaining conditions were found to significantly affect the hyporheic flow field and diminish its spatial extent as well as rates of hyporheic exchange flow. The fraction of stream water circulating through the hyporheic zone is in the range of 1 × 10−5 to 1 × 10−6 per meter stream length, decreasing with increasing discharge. Complex distributions of pressure across the streambed cause significant lateral hyporheic flow components with a mean lateral travel distance of 20% of the longitudinal flow paths length. We found that the relationship between pool‐riffle height and hyporheic exchange flow is characterized by a threshold in pool‐riffle amplitude, beyond which hyporheic exchange flow becomes independent of riffle height. Hyporheic residence time distributions (RTD) are log‐normally distributed with medians ranging between 0.7 and 19 h.